2022
DOI: 10.1039/d2ta00601d
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a self-supporting skeleton decorated with dual lithiophilic Sn-containing and N-doped carbon tubes for dendrite-free lithium metal anodes

Abstract: The commercial application of lithium (Li) metal batteries is hindered by Li dendrite related severe safety issues. Herein, a functional self-supporting skeleton decorated with dual lithiophilic Sn-containing and N-doped carbon...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, the XPS results show that there are CO, C–O groups in the ERGO@Cu/PA mesh, with an obvious oxygen doping level. Mukherjee et al and Wang et al , systematically studied the role of structural defects and oxygen-containing groups in the graphene lattice in inducing Li deposition through theoretical calculation and experimental characterization. It is found that Li is preferentially adsorbed to these topological defects in a stable form and acts as a nucleation site for further deposition to induce uniform deposition of Li.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the XPS results show that there are CO, C–O groups in the ERGO@Cu/PA mesh, with an obvious oxygen doping level. Mukherjee et al and Wang et al , systematically studied the role of structural defects and oxygen-containing groups in the graphene lattice in inducing Li deposition through theoretical calculation and experimental characterization. It is found that Li is preferentially adsorbed to these topological defects in a stable form and acts as a nucleation site for further deposition to induce uniform deposition of Li.…”
Section: Resultsmentioning
confidence: 99%
“…For the bottleneck of uncontrollable Li dendrite, several different strategies were used to suppress dendrite growth and enhance the cycling stability, modifying a strong artificial SEI film on the Li interface as a blocking layer for dendritic growth, or homogenizing the electric field distributions on an anode interface during Li deposition through modification of the electrolyte or the introduction of additives, as well as reducing the Li nucleation overpotential and homogenize Li deposition by employing lithiophilic materials. Besides, the 3D Cu current collector can inhibit the growth of Li dendrite and effectively alleviate the volume expansion through the combination with Li metal (electrodeposition, melting, and rolling), which improves the cycling stability of the Li metal battery, as well as decreases the excessive use of Li foil to a proper extent, reducing the production cost and security risks.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the lithiophilic hosts with different heteroatom doping and their corresponding electrochemical performances are presented in Table 1. Single heteroatom doping N-doped carbon substrates are widely used as lithiophilic hosts to guide regular Li deposition [76,77] . In these doped structures, N-containing species such as pyrrolic and pyridinic nitrogen, exhibit strong binding energy with Li + .…”
Section: Heteroatom Doping Of Lithium Hostsmentioning
confidence: 99%
“…; 600 h 1 C; 200 cycles [76] DLCTs N-doped carbon tubes 3 mA•cm -2 ; 3 mAh•cm -2 ; 300 cycles; 99.3% 2 mA•cm -2 ; 2 mAh•cm -2…”
Section: Ngmentioning
confidence: 99%
“…The above discussion indicates that adjusting the asymmetrical elements in the above space and dynamic factors during phase transitions is key to regulating thermal hysteresis magnitude in practical applications. Doping methods can achieve this goal [39][40][41]. Adding some extra substances might adjust the nucleation and growth processes of the minority phase in the majority phase.…”
mentioning
confidence: 99%